2002
DOI: 10.1038/416716a
|View full text |Cite
|
Sign up to set email alerts
|

Rapid electroplating of insulators

Abstract: Electrochemical techniques for depositing metal films and coatings have a long history. Such techniques essentially fall into two categories, with different advantages and disadvantages. The first, and oldest, makes use of spontaneous redox reactions to deposit a metal from solution, and can be used on both insulating and metallic substrates. But the deposition conditions of these processes are difficult to control in situ, in part because of the variety of salts and additives present in the solution. The seco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
52
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(58 citation statements)
references
References 13 publications
6
52
0
Order By: Relevance
“…Similarly to the silver electrodes, the structures grew rapidly but appeared to twist as they grew. These structures are similar to those reported recently during electroplating of insulators [15]. In addition we found that dipping the slides in 0.001 mg/dl SnCl 2 for 30 min, before electrolysis, resulted in structures that were firmly bound to the glass during working.…”
Section: Silver Fractal-like Structures On Glasssupporting
confidence: 90%
See 1 more Smart Citation
“…Similarly to the silver electrodes, the structures grew rapidly but appeared to twist as they grew. These structures are similar to those reported recently during electroplating of insulators [15]. In addition we found that dipping the slides in 0.001 mg/dl SnCl 2 for 30 min, before electrolysis, resulted in structures that were firmly bound to the glass during working.…”
Section: Silver Fractal-like Structures On Glasssupporting
confidence: 90%
“…However, in many applications of fluorescence, it would be advantageous to have localized silver deposition for spatially selective analysis, such as for lab-on-a-chip technologies [10,11]. Localized silver colloid formation has been accomplished with reagents in laminar flow [12], by nanolithography [13,14], and by electroplating on insulators [15]. Given the extensive use of roughened silver electrodes for surface-enhanced Raman scattering (SERS) [16,17], we investigated their use for spatially selective MEF, given the typically high surface areas of fractal-like structures.…”
Section: Introductionmentioning
confidence: 99%
“…This treatment resulted in the formation of fractal-like structures as recently reported. 17 These freshly generated silver surfaces were allowed to bind a protein human serum albumin (HSA) which had been heavily labeled with fluorescein isothiocyanate (FITC), resulting in self-quenching of the fluorescein. We found the intensities of FITC-HSA were increased over 100-fold when bound to these structures.…”
Section: Introductionmentioning
confidence: 99%
“…Micrometallic patterns on non-conducting surfaces, such as polymers, plastics, glasses, and ceramics are the topic of keen interest in both the scientific research community and microelectronic industry. Various methods based on masking, direct writing processes, and electrochemical techniques have been successfully applied for microscale metallic patterning of insulator surfaces [1][2][3]. Meanwhile, several laser-assisted direct processes have been established to generate metallic micropatterns on various insulators.…”
Section: Introductionmentioning
confidence: 99%